Novel method of spread spectrum communication - Jia-fang KANG; Hong-xing WANG; Zhi-yong ZHAO; Zhong-yang MAO; Xi-guo LIU; Chuan-hui1 LIU (Tongxin xuebao)
As the bandwidth efficiency of traditional spread spectrum modulation is quite low,a novel spread spectrum communication method,which uses the relative position of the spread spectrum modulation symbol to carry information was presented,and the method establishes the relationship between the information transfer rate and the spreading code or the transmission bandwidth.Theoretical analysis and simulation results show that the modulation method can not only greatly improve the bandwidth efficiency of the spread spectrum system,but also effectively combat broadband,narrow-band or other spread spectrum interference.This method provides some novel ideas for the future research of spread spectrum communications.